a=16
b=a*3+a/2=3*16+16/2=48+8=56
c=b-a/4=56-16/4=56-4=52
c=B-a+c=56-16+52=92
a=a-c-2+b*2=16-92-2+56*2=112-78=34
Если переменна принимает новое значение, то теперь только оно считается
В итоге
a=34
b=56
c=92
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
a=16
b=a*3+a/2=3*16+16/2=48+8=56
c=b-a/4=56-16/4=56-4=52
c=B-a+c=56-16+52=92
a=a-c-2+b*2=16-92-2+56*2=112-78=34
Если переменна принимает новое значение, то теперь только оно считается
В итоге
a=34
b=56
c=92